HUBUNGAN ANTARA KECERDASAN EMOSI DAN EMPATI DENGAN ALTRUISME PADA SISWA KELAS XI MIPA SMA N 3 DEMAK - Igo Masaid Pamungkas; Muslikah Muslikah (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2019)
This study was to determine the relationship between emotional intelligence and empathy for altruism in class XI of Mathematics and Natural Sciences in SMA N 3 Demak, Central Java. The method used is quantitative. Where the source of the initial research researchers conducted interviews with BK teachers in schools, which was followed up with the distribution of psychological scales in the second study and documentation. Furthermore, data analysis was performed using quantitative data analysis. Data validity test is carried out with the application of SPSS 21. The results of the data test results in this study can be useful for BK teachers where it can be a means of making new breakthroughs in providing counseling services in the private and social fields that can be applied both with classical services, group guidance or counseling group.